Microcredit matters - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Financial services for low-income clients is a hot topic in this, the International Year of Microcredit, and there is no shortage of information either for those wanting to set up microcredit schemes, or for those hoping to find out how to benefit from on